KUALITAS PELAYANAN RAWAT INAP RUMAH SAKIT UMUM DAERAH MOKOPIDO TOLITOLI - Gafar, Masrin (Katalogis, 2016)
This study aims at determining The Quality of Inpatient Services of Mokopido Regional Public Hospital Tolitolii. This study uses a qualitative research method, in which the data and the information were collected by using a Likert scale instrument and interviews with selected informants. The results show that Mokopido Public Hospital Tolitoli still lacks in the quality of service because of the research indicators of speed and timeliness of services must be improved so that patients and their families feel the optimum service from hospital personnel so as to provide effective services. Ease of service will be created if the availability of supporting facilities in health care but in fact Mokopido PublicÂ Hospital still lacks of health facilities that can inhibit good services for patients and their families for example in the medical examination, the pharmacy facilities, the facilities of care room and etc. This is certainly going to disrupt the excellent services for patients. As well as providing a fair service without making a distinction between the service of underprivileged patients and patients who are in good economic condition. The quality of services should be improved to get a positive response from patients and their families so that the hope of achieving the satisfaction of health services at the hospital can be created. The provision of hospital health care facilities which are in direct contact to the needs of health services including the availability of drugs, hospital pharmacy facilities, and supporting facilities in medical examinations for patients.